Somatic characteristics in relation to meeting recommended physical activity in overweight and obese women aged 30-60 years - Tereza Sofková; Miroslava Přidalová (Palacký University Olomouc, 2015)
Background: Physical activity (PA) can provide health benefits and thus reduce the risk of complications from obesity and improve mental well-being. We consider body composition as an acceptable indicator of the functional condition of the body. Aims: Our research objective was to analyse selected body composition fractions in relation to meeting recommended PA in overweight and obese women. Methods: 221 women participated in our study, divided in two age groups: 30 to 44.9 years (Maturus I, n = 118) and 45 to 60 years (Maturus II, n = 103). Each age group was further differentiated by sub-groups (adequate and inadequate PA) according to the achieved PA level (medium PA: 3 to 6 MET; ≥ 150 min/week). To determine the PA parameters within one week the ActiGraph GT1M accelerometer was used. The InBody 720 body composition analyser was used to determine body composition parameters. Descriptive characteristics and data analysis were carried out using Statistica 10.0. Differences were compared by the Student's t-test. Statistical significance level was set at α < .05. Results: Younger women who achieved adequate PA reached lower average values of body fat mass and visceral fat area than women with inadequate PA. Higher average values of the fat-free mass, body cell mass and skeletal muscle mass were found in older women with adequate PA in comparison with women with inadequate PA. Conclusions: The research study verified a positive relationship between meeting the recommended PA level and its impact on body composition health risk indicators. A positive approach to the PA may lead to a decrease in health problems associated with excess weight and obesity.